Analysis Online Learning at SD Muhammadiyah 3 Ikrom Wage During the Covid-19 Pandemic - Banafsa Zulfa Zakiyyah; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The spread of the covid-19 virus in Indonesia has caused schools to halt the process of direct learning. Rather, learning is done through long-term learning or from home study. Online and long-distance learning requires qualified and readily available technological assistance. Learning through zoom or Google meetings is a highly effective learning strategy, currently in force for the purpose of responding to technological advances and education. However, the question of human resources in Indonesia, especially students, is still very complicated. Teachers also experience many obstacles in the learning process. Thus, learning activities during covid-19 in online form, aimed at improving teachers' competence skills at SD Muhammadiyah 3 Ikrom Wage to implement online-based learning. The study was done to learn the student learning strategy at SD Muhammadiyah 3 Ikrom Wage during covid-19. This research is qualitative with survey methods. The result of this study, suggests that online learning has not been completely effective for SD Muhammadiyah 3 Ikrom Wage. The study is expected to be an evaluation material for various parties in organizing online learning at 3 icrom elementary school. It is also hoped to provide studies for others in analyzing online learning during the covid-19 pandemic.